2014
DOI: 10.1073/pnas.1415271111
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of Torsin ATPase activation

Abstract: Torsins are membrane-associated ATPases whose activity is dependent on two activating cofactors, lamina-associated polypeptide 1 (LAP1) and luminal domain-like LAP1 (LULL1). The mechanism by which these cofactors regulate Torsin activity has so far remained elusive. In this study, we identify a conserved domain in these activators that is predicted to adopt a fold resembling an AAA+ (ATPase associated with a variety of cellular activities) domain. Within these domains, a strictly conserved Arg residue present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
150
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(153 citation statements)
references
References 38 publications
3
150
0
Order By: Relevance
“…Most, including torsinA, are embedded in the luminal leaflet of the endoplasmic reticulum (ER) membrane (Jungwirth et al, 2010;Vander Heyden et al, 2011). Importantly, torsinA binds two transmembrane proteins of the ER system, LAP1 (also known as TOR1AIP1) and LULL1 (also known as TOR1AIP2 and NET9) Kim et al, 2010;Naismith et al, 2009;Zhao et al, 2013;Zhu et al, 2010), that have recently been shown to adopt a partial AAA+ domain fold and co-assemble with torsinA as subunits of an active enzyme (Brown et al, 2014;Sosa et al, 2014). The luminal domains of LAP1 and LULL1 are homologous to each other, whereas the extraluminal domains diverge .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most, including torsinA, are embedded in the luminal leaflet of the endoplasmic reticulum (ER) membrane (Jungwirth et al, 2010;Vander Heyden et al, 2011). Importantly, torsinA binds two transmembrane proteins of the ER system, LAP1 (also known as TOR1AIP1) and LULL1 (also known as TOR1AIP2 and NET9) Kim et al, 2010;Naismith et al, 2009;Zhao et al, 2013;Zhu et al, 2010), that have recently been shown to adopt a partial AAA+ domain fold and co-assemble with torsinA as subunits of an active enzyme (Brown et al, 2014;Sosa et al, 2014). The luminal domains of LAP1 and LULL1 are homologous to each other, whereas the extraluminal domains diverge .…”
Section: Introductionmentioning
confidence: 99%
“…The luminal domains of LAP1 and LULL1 are homologous to each other, whereas the extraluminal domains diverge . Like torsins, proteins similar to LAP1 and LULL1 have been identified across animal phyla and might have co-evolved to function together with torsins (Brown et al, 2014;Sosa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1A and 6A), we consider a major role in counteracting protein misfolding unlikely. Interestingly, several of the Torsins (Tor2A and Tor3A in humans and mice) do not harbor a hydrophobic domain, and TorA variants deprived of their hydrophobic domains retain ATPase activity (16,17), suggesting that mobilized TorAp could have a function that is distinct from its precursor.…”
Section: Discussionmentioning
confidence: 99%
“…TorsinA is partitioned between the ER and the contiguous perinuclear space of the nuclear envelope, and its localization is controlled in part by its association with LAP1 and LULL1, type II transmembrane proteins residing in the nuclear envelope and ER, respectively (12)(13)(14). Another unusual property of Torsins is that they lack significant basal ATPase activity in isolation and are tightly regulated by LAP1 and LULL1, which integrate into the Torsin ring via AAA-like domains to trigger ATP hydrolysis through an active site complementation mechanism (15)(16)(17). Thus, Torsins and their ATPase activating cofactors form a composite, membrane-spanning assembly.…”
mentioning
confidence: 99%
See 1 more Smart Citation